Pelatihan Pembuatan Sabun Wajah bagi Pemberdayaan Ibu PKK di Desa Cikarageman, Kabupaten Bekasi, Jawa Barat - Heny Herawati; Euis Bandawaty; Patriandari, Patriandari; Chusnah, Chusnah; Sri Lestari (Pusat Riset dan Inovasi Nasional, 2025)
Since the era of COVID-19 until now, maintaining personal hygiene has become a shared obligation globally. In Indonesia, soap is an essential item for both personal hygiene and environmental hygiene. Due to the great public interest in soap, especially facial soap, there are now more choices for businesses to make soap for the local market. Empowering the surrounding community, especially the PKK women's organization, to make facial soap can be done independently or in groups because the method of manufacture is quite simple. The general public's knowledge of the components and methods of making facial soap is still very minimal. This community service activity aims to teach PKK women’s how to make face soap and give them insight into home-based business options. PKK women in Cikageman Village, Setu, Bekasi Regency became a group of activity partners. This activity is expected to be able to improve people's welfare, especially in the economic sector, as well as increase knowledge and independence in entrepreneurship. This community service activity uses a strategy that includes partner coordination, counseling, assistance in making face soap, evaluation, and follow-up. The end result of this community service activity is in the form of facial soap products that have been packaged and distributed to local residents, as well as partner groups who already have skills in producing face soap independently.